Unprotected Land Ownership Rights in Corporate Land Acquisition - Lego Karjoko; Nabila Rahma Safitri; Ravi Danendra (Contrarius, 2026)
Land ownership conflicts in Indonesia frequently emerge in plantation regions when local communities cultivate land in fact while corporations assert formal legal control over the same land. This situation generates agrarian disputes that expose structural tensions between the formal land certification regime and long-established patterns of community land use. This study examines the philosophical orientation underlying judicial reasoning in adjudicating disputes concerning Land Use Rights held by PT Perkebunan Nusantara Persero and evaluates the degree of legal protection granted to communities that cultivate land without formal certificates. The research applies a normative legal method through statutory and case approaches. The study relies on primary and secondary legal materials gathered through systematic literature review and analyzes them using deductive reasoning and interpretative analysis. The findings demonstrate that judicial panels in five cases placed primary emphasis on formal legal certainty by prioritizing documentary evidence of title and by disregarding factual realities related to community cultivation. This approach directs adjudication toward procedural compliance and limits consideration of substantive justice and social utility. The analysis further shows that the legal system has not provided adequate protection for affected communities. Effective preventive protection requires clearer regulatory arrangements governing land control by communities and state-owned enterprises. Effective repressive protection requires judges to assess both formal documentation and material evidence in a balanced manner. The study concludes that current judicial practice has not achieved equitable legal protection for communities engaged in cultivated land use.